2018
DOI: 10.1177/0163278718796153
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Systematic Review of Public–Private Partnership in Promoting Physical Activity

Abstract: The purpose of the study is to conduct a comprehensive review of public-private partnership (PPP) literature that pertains to promoting physical activity. A qualitative systematic review guided data search and screening process, and the findings were synthesized and interpreted using a qualitative content analysis method. Literature was searched from 16 academic and 6 gray literature databases. A total of 1,117 articles were initially searched, full texts of 186 articles were assessed, and 13 articles that met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…In other cases, such an approach made securing buy‐in problematic, particularly within LHDs, because it was not consistent with the way these organisations determined priorities and how they themselves are evaluated. A qualitative systematic review of public‐private partnerships for promoting physical activity by Lee et al (2018) also found differences in institutional practices as a key challenge to implementing and sustaining partnerships 28 . The challenge of autonomy versus guidance was amplified by the fact that the stakeholder focal points (eg health promotion/ project officers) for MHN within stakeholders were usually relatively junior within their organisation, making it more difficult for them to influence the decisions of management.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, such an approach made securing buy‐in problematic, particularly within LHDs, because it was not consistent with the way these organisations determined priorities and how they themselves are evaluated. A qualitative systematic review of public‐private partnerships for promoting physical activity by Lee et al (2018) also found differences in institutional practices as a key challenge to implementing and sustaining partnerships 28 . The challenge of autonomy versus guidance was amplified by the fact that the stakeholder focal points (eg health promotion/ project officers) for MHN within stakeholders were usually relatively junior within their organisation, making it more difficult for them to influence the decisions of management.…”
Section: Discussionmentioning
confidence: 99%
“…The technical definition of a PPP varies broadly among different authors, areas of knowledge, and countries 14,19 . In practical terms, these partnerships are joint initiatives between 2 sectors (public and private), with a specific focus (e.g., health, economics, politics), and in a given level of action (e.g., local, national, global) 2 , being better contextualized as a mutual interest relationship rather than a sponsorship or service-providing contract.…”
Section: Public-private Partnershipsmentioning
confidence: 99%
“…This study aims to present the importance of public-private partnerships in health promotion through physical activity. A comprehensive overview of some successful examples of PPPs that promote physical activity interventions has been recently published 19 . Therefore, instead of reviewing cases, we will focus on the conceptual framework behind these PPPs, discussing their main characteristics and the benefits of their implementation to the public and private entities, as well as to the target population.…”
Section: Introductionmentioning
confidence: 99%
“…PPPs is used as an umbrella term for the continuum of voluntary cooperative arrangements between public and private institutions, which entails all involved partners agreeing to collaborate to achieve a common purpose 8 20. By bringing together different perspectives across institutions, innovative solutions based on collaborative efforts and technological development can be introduced 5 6 20–22. The value of partnerships for addressing social inequality in health has further been highlighted in the United Nations Sustainable Development Goals, Goal 17, ‘Partnerships for the goals’ which aims to “Strengthen the means of implementation and revitalize the global partnership for sustainable development”23 (p24).…”
Section: Introductionmentioning
confidence: 99%